Effects of hetero‐armed star‐shaped PCL‐PLA polymers with POSS core on thermal, mechanical, and morphological properties of PLA. Issue 29 (11th March 2021) - Doganci, Merve Dandan; Caner, Derya; Doganci, Erdinc; Ozkoc, Guralp
Abstract: In this study, AB type‐heteroarm star‐shaped poly( ε ‐caprolactone)‐poly(lactic acid) (PCL‐PLA) polymers with polyhedral oligomeric silsesquioxane (POSS) core ((PCL)4 ‐POSS‐(PLA)4, coded as SPLA) were synthesized successfully by using ring opening polymerization and click chemistry techniques together. The synthesized polymers were compounded with commercial PLA at different blending ratios (PLA/SPLA = 100/0, 95/5, 90/10, and 80/20% wt). The effects of heteroarm SPLA polymers having different arm lengths ( n = 10, 20, 30, and 50) on morphological, mechanical, and thermal behaviors of PLA were investigated. It is determined that SPLA polymers with four PLA and four PCL arms on its structure enhanced mechanical properties of PLA. The tensile modulus decreased, and lowest modulus values were observed with blends prepared at 80/20 ratio. Elongation at break values increased in all blends, maximum increment was observed with 1, 4‐phenylene diisocyanate (PDI) containing SPLA20 blends prepared at 90/10 ratio. This result showed that SPLA20 had optimum chain length for chain extension reactions of between PLA chains. Besides, a trade compatibilizer PDI was utilized to enhance the intercompatibility of binary polymer blends. Abstract :